Pengembangan Media Pembelajaran Video Animasi Berbasis Kearifan Lokal di Sekolah Dasar - Kasmawati, Kasmawati; L. Parisu, Chairan Zibar; Sisi, La; Eka Dayanti, Wa Ode; Ahmad, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study aims to develop local-based animated video learning media for Civics learning in Class V SD Negeri 13 Tinanggea. The specific aim of the research is to find out the validity of the media and the practicality of the known responses from teachers and students with the existence of these learning media. The type of research used is Research and Development (R&D) or research and development according to the Borg and Gall model. The results of this study indicate that the video animation media developed using the Borg and Gall model is declared valid. The validity level of local-based animated video learning media is based on research, including: 1) media experts get a percentage of 90.62% in the